2018
DOI: 10.17706/jcp.13.3.271-278
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Method for Evaluating Reconstructed One-Dimensional Bifurcation Diagrams

Abstract: We describe a quantitative method for evaluating reconstructed 1-dimensional bifurcation diagrams. We estimate the oscillatory patterns of time-series data by reconstructing the bifurcation diagrams from time-series data alone. Such reconstruction can be used for real-world systems that have variable parameters, such as electric current and power, temperature, pressure, and concentration. In the conventional method, the reconstructed bifurcation diagram is qualitatively compared with the original one. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In the BD reconstruction, time-series predictors are trained to model the obtained time-series data sets of all components, and the method allows the attractors of all components to be estimated when the bifurcation parameter values are changed. We reconstructed the BDs for various systems and numerical conditions using time-series data sets of a component in [8][9][10][11][12][13][14]. In this study, we show that the reconstruction requires a shorter length of training data when using time-series data sets of all components than when using the time series of only one component, compared by the previous studies.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…In the BD reconstruction, time-series predictors are trained to model the obtained time-series data sets of all components, and the method allows the attractors of all components to be estimated when the bifurcation parameter values are changed. We reconstructed the BDs for various systems and numerical conditions using time-series data sets of a component in [8][9][10][11][12][13][14]. In this study, we show that the reconstruction requires a shorter length of training data when using time-series data sets of all components than when using the time series of only one component, compared by the previous studies.…”
Section: Introductionmentioning
confidence: 66%
“…Given its extremely high training speed and good generalization, we use the ELM as a time-series predictor. In previous work, we showed that the ELM is useful for reconstructing BDs [8][9][10][11][12][13].…”
Section: Extreme Learning Machinementioning
confidence: 99%
See 1 more Smart Citation